THE EFFECT OF CASH FLOW AND CURRENCY EXCHANGE RATE ON FINANCIAL DISTRESS - Anggun Putri Romadhina; Maulida Nur Fitriani; Revan Andhitiyara (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2022)
This study aims to test and obtain empirical evidence of the effect of cash flow and currency exchange rates on financial distress. This research was conducted at trading companies listed on the Indonesia Stock Exchange (IDX) during the 2014-2018 period. This research is a quantitative study using secondary data, namely data obtained from the company's annual financial statements that have been published by the Indonesia Stock Exchange (IDX). The population in this study are trading companies listed on the Indonesia Stock Exchange (IDX) during the 2014-2018 period. Sampling using purposive sampling method and obtained a sample of 51 companies. Data analysis used in this research is descriptive statistical analysis, classical assumption test using normality test, autocorrelation test, multicolonierity test, heteroscedasticity test, multiple linear regression analysis and hypothesis testing using the F test, T test and determination coefficient R² test. Processed with the help of the SPSS version 24 statistical program. The test results using a partial test show that cash flow proxied using operation cash flow is significant against financial distress and currency exchange rates are proxied using between significant profit comparisons to financial distress. Simultaneous test results show cash flow and currency exchange rates have a joint effect on financial distress. The test results using a partial test show that cash flow proxied using operation cash flow is significant against financial distress and currency exchange rates are proxied using between significant profit comparisons to financial distress. Simultaneous test results show cash flow and currency exchange rates have a joint effect on financial distress. The test results using a partial test show that cash flow proxied using operation cash flow is significant against financial distress and currency exchange rates are proxied using between significant profit comparisons to financial distress. Simultaneous test results show cash flow and currency exchange rates have a joint effect on financial distress